Antimicrobial resistance and recurrent bacterial urinary tract infections in hospitalized patients following kidney transplantation: A single‐center experience. Issue 4 (9th June 2020) - Greissman, Samantha; Mattiazzi, Adela; Mendoza, Maria; Natori, Yoichiro; Grady, Mackenzie; Quinonez, Jose; Zukerman, Ryan; Camargo, Jose F.; Morris, Michele I.; Simkins, Jacques; Guerra, Giselle; Abbo, Lilian M.
Abstract: Purpose: The burden of urinary tract infections (UTIs) and risk factors for developing infections with multidrug resistant organisms (MDROs) post‐kidney transplantation (KT) are poorly understood. Methods: Single‐center retrospective cohort study (January 2015‐December 2017) evaluating first and recurrent episodes of bacteriuria and subsequent analysis of episodes caused by MDROs up to 6 months post‐KT. Donor and recipient variables were reviewed. Results: A total of 743 adults underwent single KT during the study period, and 106 patients were hospitalized with bacteriuria. 45% were asymptomatic in their first episode. 73.6% had a single episode, and 26.4% had 2 or more episodes. A total of 28 patients had recurrent episodes; 64.3% had an MDRO on the first episode and 78.6% on the second episode. Escherichia coli was the most common organism isolated, 88.5% were resistant to trimethoprim‐sulfamethoxazole (TMP‐SMX), 9.3% were extended‐spectrum beta‐lactamase (ESBL) producers, and 38.1% were MDROs. Body mass index ≥30 was significantly associated with the presence of MDROs in both univariate and multivariate analyses (RR 1.37, 95% CI 1.01‐1.88; OR 3.26, CI 1.29‐8.25). A total of 12 donors had bacteremia or bacteriuria and 6 (50%) with E coli . A total of 10 KT recipients received antibiotic prophylaxis to prevent donor‐derived infections. Conclusions: Our results suggest that a significant proportion of patients develop recurrent bacteriuria post‐transplantation; of those, more than half caused by MDROs. There is a possible association between obesity and MDROs in KT recipients that merits further investigation. With the global crisis in antimicrobial resistance, innovative strategies are needed to prevent and treat UTIs in KT patients.